A comparative assessment of maxillary perfusion between two different Le Fort I osteotomy techniques. Issue 3 (March 2015) - Sakharia, A.; Muthusekar, M.R.
Abstract Compromised maxillary perfusion following Le Fort I osteotomy is a potentially serious complication resulting in hard and/or soft tissue loss. The aim of this study was to compare the change in perfusion between two techniques of posterior maxillary disjunction by intraoperative measurement of maxillary gingival blood flow (GBF). Further, we sought to correlate the association of the movement of the maxilla and estimated blood loss as factors. The study population comprised 38 individuals, divided equally into two groups: a pterygoid disjunction group and a third molar socket disjunction group. GBF was measured using Doppler flowmetry. A P-value of <0.05 was considered significant. There was a significant drop in GBF in both groups. However, there was no significant difference between the groups based on magnitude of blood flow drop. Superior repositioning of the osteotomized maxilla caused the greatest drop in GBF, which was statistically significant. There was significantly less blood loss in the pterygoid disjunction group. In conclusion, Le Fort I osteotomy causes a significant decrease in GBF. The technique used for posterior maxillary disjunction does not influence the magnitude of drop in perfusion. There is a significant correlation of other factors such as the effect of superior repositioning of the maxilla and blood loss with the osteotomy techniques.